GREEN FINANCE: THE KEY TO ACCELERATING GLOBAL ENVIRONMENTAL SUSTAINABILITY - Khodjamuratova Gulbahor Yuldashevna (Modern American Journals, 2025)
Green finance has become a crucial instrument for driving global environmental sustainability. This paper analyzes the mechanisms of green financial instruments, such as green bonds and climate funds, and their impact on promoting low-carbon investments. It explores the role of financial institutions, governments, and international organizations in creating a supportive framework for sustainable finance. By channeling capital towards environmentally responsible projects, green finance not only mitigates climate risks but also fosters economic growth that aligns with global climate goals.
Keywords: Green finance, sustainable investment, environmental sustainability, climate finance, green bonds, low-carbon economy, financial policy.